Learning Trajectory Siswa dalam Memecahkan Masalah Kelipatan Persekutuan Terkecil Ditinjau dari Kemampuan Matematika - Lydia Lia Prayitno; Agus Prasetyo Kurniawan (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2017)
This study aimed to describe students' learning trajectory to solving math problems based on student’s ability. The subject is 4th-gradestudents of Madrasah Ibtidaiyah (MI) K.H. Mas Mansyur Surabaya. The results obtained by learning trajectory are (1) high ability students, expressing the understanding of the problem orally and writing, plan two solutions process, choose to use multiples and sum between departure time and travel time, the subject re-examine every step in solving the problem. (2) medium ability students, expressing an understanding of the problem orally, planning a solution and implementing it until finding a solution, in re-examining the subject using factoring; and (3) low-ability students, expressing an understanding of the problem orally, planning a solution to finding a solution, then simply re-examining the steps taken in solving the problem.